Investigating the impact of moulage on simulation engagement — A systematic review. (May 2018) - Stokes-Parish, Jessica B.; Duvivier, Robbert; Jolly, Brian
Abstract: Background: Simulation Based Education (SBE) is used as a primer for clinical education in nursing and other health professions. Participant engagement strategies and good debriefing have been identified as key for effective simulations. The environment in which the simulation is situated also plays a large role in the degree of participant engagement. Various cues are staged within simulations to enhance this engagement process. Moulage techniques are used in current-day simulation to mimic illnesses and wounds, acting as visual and tactile cues for the learner. To effectively utilise moulage in simulation, significant expense is required to train simulation staff and to purchase relevant equipment. Objective: Explore the use of moulage in simulation practice today and its influence on participant engagement. Design: Using a systematic process to extract papers, we reviewed the literature with a critical-realist lens. Data Sources: CINAHL Complete, ERIC, Embase, Medline, PsycINFO, SCOPUS, Web of Science, Proquest, Science Direct and SAGE. Review Methods: 10 databases were systematically reviewed using the keyword "moulage" to answer the question "How does the authenticity of moulage impact on participant engagement?". 1318 records were identified prior to exclusion criterion were applied. 10 articles were targeted for review, following exclusion for English language and publication between 2005 and 2015. Results: The resulting 10 papers were assessed for quality using the Medical Education Research Study Quality Instrument (MERSQI). The majority of papers were situated in dermatology teaching, with only one nursing paper. Study participants were both undergraduate and postgraduate. Most of the studies were undertaken at a university setting. No papers comprehensively addressed whether the authenticity of moulage influences learner engagement. Conclusions: Results were limited, yet clearly outline a widely held assumption that moulage is essential in simulation-based education for improved realism and subsequent learner engagement. Despite this, there is no clear evidence from the literature that this is the case, suggesting that further research to explore the impact of moulage on participant engagement is warranted. A number of recommendations are made for future research. Highlights: Simulation based education is common in healthcare education. Moulage is a technique assumed to improve realism. There is a lack of research underpinning the use of moulage in simulation. Further research should focus on how moulage influences engagement in simulation.